Penatalaksanaan Senam Kaki Diabetes Terhadap Nilai ABI (Ankle Brachial Index) Pada Lansia : Studi Kasus - Rakhmat Aji Waluyo; Dinasti Pudang Binoriang (Jurnal Medika Nusantara, 2024)
Diabetes mellitus is a metabolic disorder characterized by increased blood glucose levels due to damage to insulin secretion, less effective insulin action or both. There are many complications that arise from diabetes, one of which can cause poor blood circulation in sufferers, especially in the legs, which can later cause peripheral arterial disease (PAD). This study uses a case report approach to evaluate the implementation of nursing for elderly people with diabetes who ex perience PAD with diabetic foot exercise and success is measured by the ankle brachial index (ABI) value. The results of this study showed that there was a change in the patient's ABI value after routinely doing diabetes foot exercises for 2 weeks, the ABI value in the first week was 0.62 (right), 0.68 (left) and in the 2nd week it was 0.68 (right ), 0.82 (left). Diabetic foot exercises are an exercise that can be done by patients suffering from DM or not because the benefits of diabetic foot exercises are to help improve blood circulation in the feet and also prevent injuries.